The Role of Price, Quality, and Brand in Consumer Perception of Durable Goods in Online Shopping: A Study in Chhattisgarh - Shrivastava, Kamlesh Kishore (Integrated Journal for Research in Arts and Humanities, 2024)
This research aims to explore the influence of price, quality, and brand on consumer perception of durable goods in online shopping, focusing on the state of Chhattisgarh. The digital marketplace has increasingly become the go-to platform for purchasing durable goods, but understanding the key factors influencing consumer behavior is essential for businesses. Through a mixed-methods approach, this study surveys a diverse population in Chhattisgarh to evaluate how these three variables—price, quality, and brand—shape their online shopping decisions. The findings provide valuable insights for e-commerce platforms, manufacturers, and marketers in tailoring their strategies for the regional market. The paper concludes with actionable recommendations for enhancing consumer satisfaction and loyalty in the online shopping ecosystem.